2019
DOI: 10.1002/ecs2.2691
|View full text |Cite
|
Sign up to set email alerts
|

Traits or habitat? Disentangling predictors of leaf‐litter decomposition in Amazonian soils and streams

Abstract: Quantifying the relative contributions of plant physicochemical traits and environmental conditions to leaf decomposition is essential to increase our understanding of ecosystem processes in forested terrestrial and aquatic habitats. This is particularly crucial in tropical rainforests that display high levels of tree diversity and environmental heterogeneity over relatively small spatial scales. For example, in Amazonia, detritus from hundreds of tree species fuels carbon cycling in watersheds, but much remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…However, the diversity of litter (Gartner and Cardon 2004;Hättenschwiler et al 2005;Oliveira et al 2019) and the local decomposition environment (Jewell et al 2015;Joly et al 2017) both have been shown to further impact the decomposition process, yet their relative contribution remains poorly documented. Most studies addressing the drivers behind the variability in litter decomposition under tropical rainforests have been carried out in the Amazon Basin (Hättenschwiler et al 2011;Nottingham et al 2018;Oliveira et al 2019;Four et al 2019). Several decomposition studies have been conducted in Central Africa (Bernhard-Reversat and Schwartz 1997;Torti et al 2001;Chuyong et al 2002;Peh 2009;Peh et al 2012), yet we still have a limited understanding of the decomposition process and its drivers for major African rainforest types, especially in the Democratic Republic of the Congo.…”
Section: Introductionmentioning
confidence: 99%
“…However, the diversity of litter (Gartner and Cardon 2004;Hättenschwiler et al 2005;Oliveira et al 2019) and the local decomposition environment (Jewell et al 2015;Joly et al 2017) both have been shown to further impact the decomposition process, yet their relative contribution remains poorly documented. Most studies addressing the drivers behind the variability in litter decomposition under tropical rainforests have been carried out in the Amazon Basin (Hättenschwiler et al 2011;Nottingham et al 2018;Oliveira et al 2019;Four et al 2019). Several decomposition studies have been conducted in Central Africa (Bernhard-Reversat and Schwartz 1997;Torti et al 2001;Chuyong et al 2002;Peh 2009;Peh et al 2012), yet we still have a limited understanding of the decomposition process and its drivers for major African rainforest types, especially in the Democratic Republic of the Congo.…”
Section: Introductionmentioning
confidence: 99%
“…low lignin contents are generally expected to exhibit fast decomposition rates, both in aquatic [22][23][24] and terrestrial systems [24][25][26]. The visible, although non-significant, trend in fungal biomass (alder > chestnut > oak) in the riparian area seems to express such intrinsic litter quality differences.…”
Section: Discussionmentioning
confidence: 99%
“…This latter was done by opening 6 mm diameter holes in each corner of the bag, thus ensuring the access of macrofaunal decomposers but preventing losses of litter caused by the holes (Salinas et al, 2011). The All the litter material was collected in the study sites from freshly fallen senescent leaves, discarding those with conspicuous damages such as fungal infections, insect galls or high herbivory (>30%), as well as very bright young leaves and highly rooted leaves with extended necrotic area (Cardenas et al, 2017;Four et al, 2019). The collected litter material was oven-dried at 60 °C during 72 h and weighted using a 0.1 mg precision scale (LX 220A scs) to measure the initial and final weights.…”
Section: Decomposition Experimentsmentioning
confidence: 99%